HUKUM PENCATATAN PERKAWINAN DAN AKIBAT HUKUMNYA :(Perbandingan Hukum Pencatatan Perkawinan Di Indonesia dan Brunei Darussalam) - Bunga Azalia Ramadhani (Universitas Warmadewa, 2024)
Marriage registration is a fundamental task or obligation for prospective husband and wife who are about to enter into a marriage, because if they do not register the marriage there will be legal consequences that will be detrimental to both parties, especially the woman. Therefore, in several countries, marriage registration is mandatory for all citizens, one of which is Brunei Darussalam. In Indonesia itself, it is also mandatory to register concerning Marriage. In this research, the issue raised is regarding the differences and similarities in the legal regulations for registering marriages and the legal consequences if they are not registration at the Civil Registration Institute in both Indonesia and Brunei Darussalam. In this writing, it is included in normative juridical research with a literature study that uses laws and regulations regarding marriage and population registration that apply both in Indonesia and Brunei Darussalam as primary legal material. This research also uses several books, scientific literature and opinions of relevant experts as secondary legal materials, as well as legal dictionaries and encyclopedias as tertiary legal materials. In Indonesia and Brunei Darussalam both require all citizens to register their marriages and have sanctions if they do not do so. However, in Brunei Darussalam a priest can be a marriage registrar, which is different from Indonesia where a priest cannot be a marriage registrar. Indonesian citizens can only register their marriage at the KUA for Muslims communities and the Civil Registrations Institute for non-Muslim communities.